O CORO EM O DÍSCOLO DE MENANDRO - Dezotti, Maria Celeste Consolin (Organon, 2010)
There is a consensus among scholars that the chorus in Menander’s time hadbecome totally detached from stage-action; its performances, marked in the Greek textby the word ΧΟΡΟΥ, separated like interludes the acts from each other within theplays; the chorus had a technical function: provide a break in the action to cover certainoff-stage events and indicate the passing of time. This paper, however, examines inDyskolos, one of Menander’s early comedies, the relation between the chorus andCnemon present in the old man’s words that makes generalizations about humanrelationships, and shows that in this comedy the chorus of the followers of the god Panwas exploited by the poet as a source of achieving various dramatic effects.